Corona Virus 229E, NL63 And OC43 Infection Of Human Monocyte-Derived Dendritic Cells: Modulation of Immune Effector Function - Lister, Erin (My University, 2009)
Virus-induced modulation of dendritic cell function is thought to be an effective mechanism for viral-immune evasion. The severe-acute respiratory syndrome coronavirus (SARS-CoV) has been shown to infected human myeloid dendritic cells (MDCs) and directly modulate the cellular cytokine production. The ability of other human coronaviruses to infect MDCs and impair cell immune function has not been assessed.
This thesis describes the infection of human MDCs with coronavirus 229E, NL63, and OC43. 229E showed productive, but limited genomic replication, nucleocapsid protein synthesis and infectious progeny release in MDCs. 229E infection stimulated IFN-α, IL-6 and MCP-1 production in MDCs, but little to no IL-12, TNF-α, IL-8, IP-10, or RANTES . 229E-infected MDCs showed poor CD80 expression, down-regulated CD86 and HLA-DR expression and were poor stimulators of CD4+ T cell proliferation. In contrast to 229E, OC43 showed persistent and productive genomic replication, nucleocapsid protein synthesis and infectious progeny release in MDCs. OC43 infection stimulated IFN-α, IL-12, IP-10 and MCP-1 production in MDCs, but little to no TNF-α, IL-6, IL-8 or RANTES . The up-regulation of maturation molecules and CD4+ T cell stimulatory capacity in OC43-infected MDCs was donor cell-dependent. In contrast to 229E and OC43, NL63 infection of MDCs was non-productive, showing no viral genomic replication, protein production or infectious progeny release. NL63 infection stimulated strong cytokine (IFN-α, IL-12, TNF-β and IL-6) and chemokine (IL-8, IP-10, RANTES and MCP-1) responses in MDCs. NL63-infected MDCs showed up-regulated CD80, CD83, CD86 and HLA-DR expression and were efficient stimulators of CD4+ T cell proliferation.
This study provides the first evidence that human coronaviruses other than SARSCo V can abrogate MDC immune effector function. It also provides the first side-by-side comparison of 229E, NL63 and OC43 and identifies the potential of 229E and OC43 to impair MDC cytokine production and T cell stimulation as a mechanism of immune response evasion.
Keywords: virus-induced modulation, dendritic cell function, viral-immune evasion, Severe-acute respiratory syndrome, coronavirus, SARS-CoV, MDCs, myeloid dendritic cells, cellcular, cytokine production, 229E, IL-12, TNF, IP-10, CD4+, CD86